Logics of "Good teaching": Exploring Mathematics Education in Primary School in Sweden - Kristina Holmberg; Lisbeth Ranagården (Athens Institute for Education and Research, 2016)
The public and academic debate about mathematics education has been intensified during the last decade. In relation to this it is important to investigate what ideas concerning mathematics education that are expressed by teachers and students. The aim of this article is to study how teachers and students in primary school talk about the math book and to emphasize, discuss and problematize emerging discourses. The article is part of a larger project about mathematical education. Data consists of group conversations with 120 students and 8 teachers in two elementary schools in Sweden. The math project was supported by the National Agency for Education 2010-2012. All together 17 hours of video and audio documentation were produced. The theoretical framework is built on poststructuralist and social constructionist theory and two approaches to discourse analysis are applied; the micro oriented discursive psychology as formulated by Potter, and discourse theory as formulated by Laclau and Mouffe. Findings show three prominent discourses emerging from the empirical data: School mathematics, Balance and Mathematical ontology. Related to earlier research in mathematics education this article represent a shift of interpretation as it highlights how teachers and students themselves are talking about and describing what is desirable and not. The results are then discussed with respect to quality in mathematics education.